Strategic HR Practices in Some Organizations in the Philippines - Supangco, Vivien (Philippine Management Review; Vol 19 (2012), 2012)
This study describes strategic human resource (HR) practices in a convenience sample of organizations in the Philippines, and compares results of Cranet surveys conducted in 2003 and 2008.  Characteristics of sample organization as well as their strategic HR practices have generally remained the same since 2003.  A formalized strategic planning process generally obtains, but involvement of HR from the outset of business strategy formulation does not yet characterize the majority of these organizations. HR practices that have basically remained the same include, among others, the following: the most common source of HR head is HR specialists from outside the organization, and responsibility of HR policy decisions is shared between HR and line managers. On the other hand, a few practices have changed in the following manner: increase in the application of HRIS (human resource information system) in payroll, time and attendance, but decrease in application in recruitment and selection.  In addition, performance appraisal is practiced across all staff categories in 2008; in 2003 only the managerial and professional/technical workers are generally appraised through a formal system.
Keywords: Cranet; Philippines; HR practices; staffing; compensation; training and development; employee relations and communication